The internal melting of landfast sea ice in Prydz Bay, East Antarctica. (1st July 2022) - Zhao, Jiechen; Cheng, Bin; Vihma, Timo; Lu, Peng; Han, Hongwei; Shu, Qi
Abstract: Summertime internal melting of Antarctic sea ice is common due to the penetration of solar radiation below the snow and ice surface. We focus on the role of internal melting and heat conduction in generating gap layers within the ice. These often occur approximately 0.1 m below the ice surface. In a small-scale survey over land-fast sea ice in Prydz Bay, East Antarctica, we observed, for the first time, gap layers 0.6–1.0 m below the surface for both first-year ice and multi-year ice. A 1D snow/ice thermodynamic model successfully simulated snow and ice mass balance and the evolution of the gap layers. Their spatial distribution was largely controlled by snow thickness and ice thickness. A C-shaped ice temperature profile with the lowest values in the middle of the ice layer resulted in heat flux convergence causing downward progression of the internal melt layer. Multidecadal (1979–2019) seasonal simulations showed decreasing air temperature favored a postposed internal melting onset, reduced total internal melt, and delayed potential ice breakup, which indicated a higher chance for local coastal ice to be shifted from first-year ice to multi-year ice.